Philosophy as passion and task - Burnett, Henry (Argumentos - Revista de Filosofia, 2022)
Starting from the reception of Oswald de Andrade's work in Benedito Nunes' critique, the text reflects on the paths of training in philosophy in Brazil, recovering some key texts by the philosopher from Pará. With this, we intend to point out some paths opened by its innovative perspective of bringing together philosophy and poetry within a Brazilian context.